The Effect of the Riize Brand Ambassador and Brand Image on Purchase Decision of Richeese Nabati Products on Gen Z in Surabaya - Dinda Audelia Sabina Putri; Rizky Dermawan (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to assess the effect of the RIIZE brand ambassador and brand image on the purchase decision of Richeese Nabati products among Gen Z in Surabaya City. The employed research methodology is quantitative. The sample method utilized was non-probability sampling with purposive sampling. The population in this research is consumers of Richeese Nabati products who are included in the Gen Z category in Surabaya City and with a sample of 108 respondents. Data gathering methods encompass basic data obtained through surveys on a Likert scale, as well as secondary data through literature studies from relevant sources. The data analysis method uses the SmartPLS application with the PLS based SEM method. The results showed that the RIIZE brand ambassador and brand image had a positive and significant effect on the purchase decision of Richeese Nabati products on Gen Z in Surabaya City.